Methodological trends in studies based on verbal autopsies before and after published guidelines - Rohina Joshi; Andre Pascal Kengne; Bruce Neal (The World Health Organization, 2009)
OBJECTIVE: To report on the uptake of guidelines published in the early 1990s with specific recommendations about the design of future studies based on verbal autopsy conducted for mortality surveillance. METHODS: We conducted a systematic literature search of all verbal autopsy studies published before January 2006 and extracted from the studies a standard set of data. We then compared studies designed before and after the recommendations were issued in terms of seven key methodological indicators. FINDINGS: We found 102 studies conducted in 39 countries; 60 were designed before and 42 after the guidelines were issued. The methods used in these 102 studies varied considerably. While some encouraging trends were noted, there is no evidence that the design recommendations have been systematically implemented. Specifically, there was no clear increase in the proportion of studies with a combined questionnaire (63% before recommendations versus 74% after; P = 0.3), a trained interviewer (70% versus 70%; P = 1.0), a suitable respondent (98% versus 100%; P = 1.0), an optimal recall period (84% versus 97%; P = 0.2), predefined algorithms (28% versus 38%; P = 0.4), an option for assigning multiple causes of death (30% versus 38%; P = 0.3), or a follow-up validation study (83% versus 72%; P = 0.7). CONCLUSION: Expert recommendations for optimal design of verbal autopsy studies have been incompletely implemented to date. Better uptake of design recommendations through enhanced collaboration between research teams is likely to produce better mortality statistics from an increasing number of verbal autopsy studies.